2017
DOI: 10.1037/ser0000120
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of technology-based mental health services for homeless youth: A qualitative study.

Abstract: Homelessness has serious consequences for youth that heighten the need for mental health services; however, these individuals face significant barriers to access. New models of intervention delivery are required to improve the dissemination of mental health interventions that tailor these services to the unique challenges faced by homeless youth. The purpose of this study was to better understand homeless youths’ use of technology, mental health experiences and needs, and willingness to engage with technology-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…This matches previous exploratory research that found positivity towards the hypothetical possibility of apps for depression and anxiety (Adkins et al . , Torous et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This matches previous exploratory research that found positivity towards the hypothetical possibility of apps for depression and anxiety (Adkins et al . , Torous et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have often focused on hypothetical attitudes and expectations prior to use (Adkins et al . , Torous et al . ), or on design features and usability of one app in isolation (Grist et al .…”
Section: Introductionmentioning
confidence: 99%
“…Because the activation of device sensors is associated with additional power demands, limited battery capacity—or the ability to charge devices on demand—may also be relevant, for example in homeless youth. 104 Similarly, the assumption that smartphones are “always carried and always on” may not be valid in older populations, limiting their ability to derive value from digital phenotyping strategies that rely on continuous signals. Recognizing that there may be constraints associated with specific populations does not mean that nothing can be done.…”
Section: Introductionmentioning
confidence: 99%
“…Various United Nations estimates show that between 100 to 150 million people experience different forms of homelessness worldwide [1][2][3]. This is a concern because the homeless population is susceptible to various health problems due to their sleeping conditions [4][5][6][7][8][9][10], and they are a marginalised group with poor access and low usage of health care services [5].…”
Section: Introductionmentioning
confidence: 99%